Pengaruh Suhu Dan Lama Pengeringan Terhadap Karakteristik Teh Celup Herbal Daun Gonda (Sphenoclea zeylanica Gaertn.) - Audi Simbolon, Christofer; Yusa, Ni Made; Kencana Putra, Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
This study aims to determine the effect of temperature and proper drying time to produce gonda leaf herbal tea bags with the best characteristics. This research used a completely randomized factorial design with two factors, namely drying temperature (50oC, 60oC, 70oC) and drying time (180 minutes, 210 minutes, 240 minutes). There are 9 treatment combinations, each treatment combination is repeated 2 times so that the number of treatment combinations is 18 experimental units. The data obtained were analyzed by analysis of variance. If the treatment had a significant effect, it would be followed by the Duncan test. The results showed that interaction beetwen drying temperature and time treatment had a very significant effect (P<0,01) on moisture content, total phenolic content, antioxidant activity and hedonic taste of gonda leaf herbal tea, have a significant effect (P<0,05) on total flavonoid content and hedonic colour and also had no significant effect (P>0, 05) to test the hedonic aroma and overall acceptance. The drying temperature of 50oC with a drying time of 240 minutes was the best temperature and drying time to produce herbal tea bags of gonda leaves with an antioxidant activity of 58.56% with IC50 1136443,36 ppm, moisture content of 6.37%, total phenolic content was 5.07 mg GAE / g, total flavonoid content was 0.84 mg QE / g, and sensory properties of colour 3.45 (slight liked), aroma 3.15 (neither like nor dislike), taste 3,65 (liked) and overall acceptance 3.15 (neither like nor dislike).